The degree of heart rate asymmetry is crucial for the validity of the deceleration and acceleration capacity indices of heart rate: A model-based study. (1st September 2016) - Pan, Qing; Zhou, Gongzhan; Wang, Ruofan; Yu, Yihua; Li, Feng; Fang, Luping; Yan, Jing; Ning, Gangmin
Abstract: The deceleration capacity (DC) and acceleration capacity (AC) of heart rate are a pair of indices used for evaluating the autonomic nervous system (ANS). We assessed the role of heart rate asymmetry (HRA) in defining the relative performance of DC and AC using a mathematical model, which is able to generate a realistic RR interval (RRI) time series with controlled ANS states. The simulation produced a set of RRI series with random sympathetic and vagal activities. The multi-scale DCs and ACs were computed from the RRI series, and the correlation of DC and AC with the ANS functions was analyzed to evaluate the performance of the indices. In the model, the HRA level was modified by changing the inspiration/expiration (I/E) ratio to examine the influence of HRA on the performances of DC and AC. The results show that on the conventional scales ( T =1, s =2), an HRA level above 50% results in a stronger association of DC with the ANS, compared with AC. On higher scales ( T =4, s =6), there was no HRA and DC showed a similar performance to AC for all I/E ratios. The data suggest that the HRA level determines which of DC or AC is the optimal index for expressing ANS functions. Future clinical applications of DC and AC should be accompanied by an HRA analysis to provide a better index for assessing ANS. Highlights: A cardiovascular model is proposed to simulate HRA, and DC/AC. HRA is found to be increased with the elevation of inspiration/expiration ratio. Short-term DC outperforms AC when HRA is higher than 50%. On a longer time scale, HRA is absent and DC/AC perform closely.